Arbuscular Mycorrhizal Fungi-Induced Signalling in Plant Defence against Phytopathogens - Vipin Panwar2, H.K. Gogoi1, Lokendra Singh1, Md. Haneef Khan1, M.K. Meghvansi1* (Journal of Phytology, 2010)
Arbuscular mycorrhizal fungi (AMF), the ancient mutualist and biotroph of plants, improve the supply of water and nutrients, such as phosphate and nitrogen to its host plant. In exchange of this, it takes a part of photosynthate sugar to complete its life cycle. Despite having its own immune system, the plant upon pathogen attack gets weaken and needs reinforcement to fight back and become stabilize in the battle ground. AMF fulfills the need of host plant and provides with support in many ways by induction of attenuated defence signaling for combating against phytopathogen. This elevation not only makes plant more tolerant towards the attack of phytopathogen but also, enhances the genetic, biochemical and signaling factors responsible for its defence purpose. In this article, we look forward to discuss the factors, mechanisms and pathways responsible for this back-up from AMF to plants with recent experimental proof. In addition, this meta-analysis will also try to focus on areas that have recently got attention or are less known, so that, lacunae and underestimated aspects should come in front for a further systematic research. <span style="line-height: 110%; font-variant: normal !important; font-family: ";Book Antiqua";,";serif";; letter-spacing: -0.3pt; font-size: 7pt; font-weight: normal; mso-font-kerning: 0pt; mso-no-proof: no; mso-fareast-language: EN-SG; mso-ansi-language: EN-SG;" lang="EN-SG">Md. Haneef Khan et al. Arbuscular Mycorrhizal Fungi-Induced Signalling in Plant Defence against Phytopathogens. J Phytol 2/7 (2010) 53-69.